Exposure to Environmental Pollutants and Risk of Diarrhea: A Systematic Review - Eudora Nwanaforo; Cecilia N Obasi; Chiara Frazzoli; Onyinyechi Bede-Ojimadu; Orish E Orisakwe (Environmental Health Insights)
This systematic review investigates the association between environmental pollutants and the risk of diarrhea, a critical public health issue, particularly in low- and middle-income countries. The review synthesizes findings from various studies that highlight the impact of contaminants such as pesticides, heavy metals, polycyclic aromatic hydrocarbons (PAHs), microplastics, and parabens on gastrointestinal health. Following PRISMA guidelines, a comprehensive literature search across databases including PubMed, Scopus, and Google Scholar yielded 496 articles, of which 11 met the inclusion criteria for detailed analysis. The results indicate a significant correlation between exposure to specific pollutants—particularly pesticides like dichlorodiphenyltrichloroethane (DDT), PAHs, arsenic, cadmium, and microplastics—and increased incidences of diarrhea. Notably, studies revealed that prenatal exposure to DDT is linked to higher diarrhea rates among boys in urban settings, while pesticide exposure in childhood correlates with inflammatory bowel disease in adulthood. Mechanistically, these pollutants may disrupt gastrointestinal function through cholinergic effects and endocrine disruption, leading to altered gut motility and microbiome imbalances. Moreover, the review emphasizes the immunosuppressive effects of heavy metals such as mercury and cadmium, which compromise the immune response and increase susceptibility to gastrointestinal infections. Despite the identified associations, there is a notable gap in research regarding geographic distribution and pollutant impacts on health outcomes. The review underscores the necessity for public health interventions aimed at reducing exposure to these environmental pollutants to mitigate their adverse health effects. In conclusion, this systematic review highlights the urgent need for further epidemiological studies in underrepresented areas to enhance our understanding of how environmental pollutants influence public health globally. Recommendations include rigorous monitoring of pollutant levels, public health initiatives to reduce exposure, and policies that restrict emissions of harmful substances. Addressing environmental pollution is crucial for mitigating diarrheal diseases and protecting vulnerable populations from its detrimental effects.